Risk Evaluation and Damage Mitigation in Subsea Pipelines: A Literature Review of Concepts, Applications, and Challenges - Muhammad Firdaus Bin Yusup (Collaborate Engineering Daily Book Series, 2023)
Subsea pipes are one of the critical components in the oil and gas industry, which are used to transport fluids from wells to surface facilities or vice versa. Subsea pipelines can experience damage due to various factors, such as corrosion, erosion, impacts, structural failure, and others. Damage to underwater pipelines can cause leaks, fires, explosions, or even environmental disasters. Therefore, it is necessary to evaluate risks and mitigate damage to ensure the safety and feasibility of subsea pipeline operations. This article provides a literature review of the concepts, applications, and challenges associated with risk evaluation and damage mitigation in subsea pipelines. Various methods and techniques used in risk evaluation and damage mitigation in subsea pipelines are reviewed and compared. Several challenges faced in risk evaluation and damage mitigation in underwater pipelines are identified and solutions are suggested. This article also provides recommendations and suggestions for further research in this area.